2019
DOI: 10.1017/s1751731118001611
|View full text |Cite
|
Sign up to set email alerts
|

Early intervention with faecal microbiota transplantation: an effective means to improve growth performance and the intestinal development of suckling piglets

Abstract: Recent studies indicate that early postnatal period is a critical window for gut microbiota manipulation to optimise the immunity and body growth. This study investigated the effects of maternal faecal microbiota orally administered to neonatal piglets after birth on growth performance, selected microbial populations, intestinal permeability and the development of intestinal mucosal immune system. In total, 12 litters of crossbred newborn piglets were selected in this study. Litter size was standardised to 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 40 publications
5
44
0
Order By: Relevance
“…It has been shown that fecal sIgA can be quantified as a biomarker of intestinal permeability and immune functions [48]. Besides, early intervention with FMT-CS increased plasma IgG and IgM, and similar results were reported in previous studies of suckling piglets [20,35]. Our results indicate that early intervention with FMT-CS can improve the adaptive immune function of piglets.…”
Section: Early-life Intervention With Fmt-cs Promotes the Developmentsupporting
confidence: 90%
See 4 more Smart Citations
“…It has been shown that fecal sIgA can be quantified as a biomarker of intestinal permeability and immune functions [48]. Besides, early intervention with FMT-CS increased plasma IgG and IgM, and similar results were reported in previous studies of suckling piglets [20,35]. Our results indicate that early intervention with FMT-CS can improve the adaptive immune function of piglets.…”
Section: Early-life Intervention With Fmt-cs Promotes the Developmentsupporting
confidence: 90%
“…Early infancy is considered as an ideal window for gut microbial colonization [18,38]. Our previous study has validated the benefits of transplanting sow fecal microbiota to newborn piglets [20]. Here, by combining the oral administration of fecal microbiota of gestation sows with C. butyricum and S. boulardii in newborn piglets, this study for the first time focuses on the promotion of immune development through improving the gut microbiota of piglets.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations